2012
DOI: 10.4103/1319-3767.98425
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cysts : A review of literature

Abstract: Choledochal cysts are cystic dilation of extrahepatic duct, intrahepatic duct, or both that may result in significant morbidity and mortality, unless identified early and managed appropriately. The incidence is common in Asian population compared with western counterpart with more than two third of the cases in Asia being reported from Japan. The traditional anatomic classification system is under debate with more focus on etiopathogenesis and other aspects of choledochal cysts. Even though categorized under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 43 publications
4
98
0
9
Order By: Relevance
“…4 , 5 Modern imaging techniques have facilitated the diagnosis of choledochal cyst at any time from antenatal to adult life. 6 Symptoms of choledochal cyst include abdominal pain, jaundice, cholangitis, and may eventually lead to malignant transformations, so early diagnosis and proper surgical excision are very important. For many years, open excision, as the standard procedure, made great impact in the treatment of choledochal cyst.…”
mentioning
confidence: 99%
“…4 , 5 Modern imaging techniques have facilitated the diagnosis of choledochal cyst at any time from antenatal to adult life. 6 Symptoms of choledochal cyst include abdominal pain, jaundice, cholangitis, and may eventually lead to malignant transformations, so early diagnosis and proper surgical excision are very important. For many years, open excision, as the standard procedure, made great impact in the treatment of choledochal cyst.…”
mentioning
confidence: 99%
“…Pancreatic secretions will be forced into this space due to the presence of the anomalous pancreatobiliary junction. [2] Backflow of intestinal secretions results in the activation of pancreatic enzymes in the remnant cyst, which may lead to infection, stone formation, and an increased risk of malignancy. [20] A previous study demonstrated that no patients developed cholangiocarcinoma after complete cyst excision.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Presence of an anomalous junction of the pancreaticobiliary duct that allows pancreatic secretions to reflux into the biliary tree is the generally accepted etiopathogenic theory of these cysts. [2,3] Nearly 20% of choledochal cysts are present in adults, and malignant transformation is the most feared complication. [4] A 6% to 30% risk of developing malignancy is estimated in patients with choledochal cysts; the risk is low in childhood (<1%) but increases to about 30% to 40% with age greater than 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, la régénération continue de l´épithélium biliaire dénudé évolue au long court vers la métaplasie intestinale puis vers la dysplasie. Des études anatomo-pathologiques ont pu mettre en évidence des lésions hyperplasiques, dysplasiques, et carcinomes in situ disséminés illustrant l´hypothèse d´un continuum évolutif vers un stade invasif [ 11 , 12 ]. Le cas de dégénérescence que nous rapportons pourrait bien être inclus dans ce cadre là; des zones de dysplasie modérées et sévères, à différents sites de la dilatation, étaient associés à une lésion tumorale qui du reste ne dépassait pas la musculeuse.…”
Section: Discussionunclassified
“…L´adénocarcinome est le type histologique le plus fréquent (90% des cas); des formes mixtes avec des zones d´hépithéliomas malpighiens ne sont pas rares [ 2 ]. Le type papillaire aurait le meilleur pronostic [ 12 ]. Sur le plan clinique, aucun signe d´appel n´est particulier au cancer développé sur DKVB [ 3 ].…”
Section: Discussionunclassified